Large and fine scale population structure in European hake (Merluccius merluccius) in the Northeast Atlantic. (15th February 2017) - Westgaard, Jon-Ivar; Staby, Arved; Aanestad Godiksen, Jane; Geffen, Audrey J.; Svensson, Anders; Charrier, Gregory; Svedäng, Henrik; André, Carl
Abstract : Recently, there have been reports of increased abundance and landings of European hake in the northern part of the species range. Biological studies are however scarce and information about finer scale population structure important for stock assessments and fishery management is largely lacking. Here, we report on a population genetic study using neutral and outlier SNP loci assessing population structure in hake in the north-eastern parts of its range in the Atlantic. Hake samples from localities along the west coast of Norway, the Kattegat, the northern North Sea, and one locality in the Bay of Biscay were analysed using 53 SNPs, six of which were outliers potentially influenced by natural selection. We detected small-scale structure among northern samples, all of which were also distinct from Bay of Biscay hake, with the exception of a few individuals from the North Sea and the coast of Norway who clustered genetically together with Bay of Biscay hake. Our findings suggest that the present management unit of a single northern stock of hake is not biologically correct, and that there is more detail in the fine-scale population structure indicating that independent population dynamics could be expected in response to fishing patterns or changing environmental conditions.